Quercetin Promotes Diabetic Wound Healing via Switching Macrophages From M1 to M2 Polarization - Fu, Jia; Huang, Jingjuan; Lin, Man; Xie, Tingting; You, Tianhui (The Journal of surgical research, 2020)
For patients with diabetes mellitus, excessive and long-lasting inflammatory reactions at the wound site commonly lead to the delayed refractory wound healing. The polarization of macrophages in terms of M1 and M2 phenotypes is closely related to the production of inflammatory cytokines. Quercetin is traditionally recognized to have anti-inflammatory effect; however, whether quercetin modulates macrophage polarization from M1 to M2 and thus promotes diabetic wound healing remain unknown. Wounded male diabetic rats were equally divided into five groups: model group, solvent control group (10% DMSO), and three drug groups treated with quercetin (Q) at concentrations of 10 mg/mL (Q-LD [low dose]), 20 mg/mL (Q-MD [medium dose]), and 40 mg/mL (Q-HD [high dose]), respectively. The anti-inflammatory effect of quercetin on diabetic wounds was observed. Immunohistochemistry and quantificational real-time polymerase chain reaction were applied to test the changes in macrophage polarization and inflammatory responses. The wound contraction was fastest in Q-HD group. Hematoxylin and eosin (H&E) and Masson's trichrome staining revealed that fibroblast distribution and collagen deposition in quercetin-treated groups were significantly higher than those in the model group. Immunohistochemistry tests showed more CD206-positive cells and less iNOS-positive cells in quercetin-treated groups. Furthermore, the levels of proinflammatory factors in quercetin-treated groups were lower than those in the model group, whereas the levels of the anti-inflammatory factors and angiogenesis-related factors were relatively higher. In short, quercetin inhibits inflammatory reactions via modulating macrophage polarization switching from M1 to M2 phenotype, thereby accelerating the diabetic wound repair.